SbCl3-catalyzed one-pot synthesis of 4,4′-diaminotriarylmethanes under solvent-free conditions: Synthesis, characterization, and DFT studies - Bardajee, Ghasem Rezanejade (Beilstein Journal of Organic Chemistry, 2011)
A simple, efficient, and mild procedure for a solvent-free one-step synthesis of various 4,4′-diaminotriarylmethane derivatives in the presence of antimony trichloride as catalyst is described. Triarylmethane derivatives were prepared in good to excellent yields and characterized by elemental analysis, FTIR, 1H and 13C NMR spectroscopic techniques. The structural and vibrational analysis were investigated by performing theoretical calculations at the HF and DFT levels of theory by standard 6-31G*, 6-31G*/B3LYP, and B3LYP/cc-pVDZ methods and good agreement was obtained between experimental and theoretical results.
Keywords: diaminotriarylmethane; SbCl3; solvent-free reactions; synthesis; vibrational analysis